Equol enhances tamoxifen’s anti-tumor activity by induction of caspase-mediated apoptosis in MCF-7 breast cancer cells - Charalambous, Christiana (BioMed Central, 2013)
BACKGROUND: Soy phytoestrogens, such as daidzein and its metabolite equol, have been proposed to be responsible for the low breast cancer rate in Asian women. Since the majority of estrogen receptor positive breast cancer patients are treated with tamoxifen, the basic objective of this study is to determine whether equol enhances tamoxifen’s anti-tumor effect, and to identify the molecular mechanisms involved. METHODS: For this purpose, we examined the individual and combined effects of equol and tamoxifen on the estrogen-dependent MCF-7 breast cancer cells using viability assays, annexin-V/PI staining, cell cycle and western blot analysis. RESULTS: We found that equol (>50 μM) and 4-hydroxy-tamoxifen (4-OHT; >100 nM) significantly reduced the MCF-7 cell viability. Furthermore, the combination of equol (100 μM) and 4-OHT (10 μM) induced apoptosis more effectively than each compound alone. Subsequent treatment of MCF-7 cells with the pan-caspase inhibitor Z-VAD-FMK inhibited equol- and 4-OHT-mediated apoptosis, which was accompanied by PARP and α-fodrin cleavage, indicating that apoptosis is mainly caspase-mediated. These compounds also induced a marked reduction in the bcl-2:bax ratio, which was accompanied by caspase-9 and caspase-7 activation and cytochrome-c release to the cytosol. Taken together, these data support the notion that the combination of equol and tamoxifen activates the intrinsic apoptotic pathway more efficiently than each compound alone. CONCLUSIONS: Consequently, equol may be used therapeutically in combination treatments and clinical studies to enhance tamoxifen’s effect by providing additional protection against estrogen-responsive breast cancers.